Pengaruh Penambahan FAME Terhadap Parameter Density, Distillation, dan Calculated Cetane Index Pada Produk Biosolar - Oktari, Tantri; Pane, Elfira Rosa; Nugraha, Aji (Jurnal Sains Dasar, 2024)
The fossil-based fuel energy crisis in Indonesia occurred because of the high demand to meet the demand for fuel in the transportation sector but the low availability of fossil fuels which are difficult to renew. One way to overcome this is to develop alternative energy sources to reduce the use of non-renewable energy sources such as diesel fuel. The government has determined the use of alternative energy sources such as biodiesel B30 which is a mixture of diesel fuel with a FAME (Fatty Acid Methyl Esters) content of 30%. However, there is a possibility that Indonesia will increase the FAME content. The method used is density 15˚C using ASTM D-1298, distillation using ASTM D-86 and calculated cetane index using ASTM D-4737. The results showed an increase in the value of samples B0, B30, B35, and B100, obtained at a density of 15˚C, namely 0.8371 gr/ml; 0.8484 gr/ml; 0.8505 gr/ml; 0.8729 gr/ml, in distillation the boiling point increases from IBP (Initial Boiling Point) to the end point, and the CCI is 48.4; 50.0; 50.6; 58.2.